Effects of artificial deformation on cranial morphogenesis in the South Central Andes - Cocilovo, Jose Alberto (2011)
One of the most interesting issues of the interface between biology and culture is the artificial deformation of the skull. This modification is produced during early morphogenesis through the use of devices that alter the normal growth and development, to obtain a culturally established model. This paper, using a large cranial sample from the South Central Andes (1586 individuals), describes and documents a detailed morphometric study of the changes affecting the vault, cranial base, face, orbits and nasal region resulting from the tabular erect (TE), tabular oblique (TO), circular erect (CE) and circular oblique (CO) deformations with respect to the model without deformation. Data from 17 metric variables were processed by a one-way ANOVA and LSD test for paired comparisons. All of the deformation types produce significant morphometric divergence in most of the anatomical structures of the skull. The TE exhibits: a restriction of antero-posterior growth producing expansion in cranial width and height, frontal flattening, shortening of the face and cranial base, widening of the face, increased nasal and orbit height (ORH) and a foramen magnum size increase. The TO exhibits: most change reflected in the widening of the cranial vault, shortening of the cranial base and face, frontal flattening, increased nasal and ORH and foramen magnum size decrease. The CE style exhibits: a decrease in cranial width and strong increase in the cranial height, a reduction in frontal width, expansion of the cranial base and face, increased nasal and ORH, orbital widening and a foramen magnum size increase. The CO style exhibits: a decrease of the cranial vault´s width and height, expansion along its length, stretching of the cranial base and face, reduced frontal width, fronto-malar and biorbitary elongation of the face and further development of foramen magnum.